1999
DOI: 10.1093/humrep/14.6.1457
|View full text |Cite
|
Sign up to set email alerts
|

Elective cryopreservation of all pronucleate embryos in women at risk of ovarian hyperstimulation syndrome: efficiency and safety

Abstract: In a prospective randomized study, we analysed 125 patients at risk of ovarian hyperstimulation syndrome (OHSS), selected in the period between January 1996 and July 1997. All the patients had blood oestradiol concentration >/=1500 pg/ml on the day of human chorionic gonadotrophin (HCG) administration and >/=15 oocytes were collected. The patients were matched in two groups: group A, control group (n = 67), had fresh embryo transfers; group B (n = 58) had cryopreservation of all obtained pronucleate embryos. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
2
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(72 citation statements)
references
References 22 publications
1
66
2
3
Order By: Relevance
“…A trend towards higher multiple pregnancy rate was also noted in FET cycles. Two previous studies have compared cryopreservation of all embryos with either human albumin or fresh ET and in the former, higher pregnancy rate was found in FET group [16] and in the latter no difference was found [17].…”
Section: Discussionmentioning
confidence: 95%
“…A trend towards higher multiple pregnancy rate was also noted in FET cycles. Two previous studies have compared cryopreservation of all embryos with either human albumin or fresh ET and in the former, higher pregnancy rate was found in FET group [16] and in the latter no difference was found [17].…”
Section: Discussionmentioning
confidence: 95%
“…These studies, however, are limited by a lack of a comparison group [15] or details of the comparison group [16][17][18][19][20]. The choice of comparison group for this study is not necessarily to serve as a control, but is provided only to provide the background for the center's general practice and IVF outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed a similar incidence of OHSS but significantly higher PR in the cryopreservation group. Ferraretti et al [15] demonstrated that the PR and LBR rate among patients who underwent subsequent thaw of cryopreserved embryos was similar to those who underwent fresh transfer. There were no cases of OHSS among the 58 patients who underwent cryopreservation with subsequent transfer of thawed embryos, and there were 4 patients among 67 who developed OHSS in the control group.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In all, 371 thawing cycles were performed by administration of hormonal replacement therapy consisting of estradiol valerate (Progynova; Schering, Milan, Italy) at 2 mg/d from day 1 to day 5 of the menstrual cycle, 4 mg/d from day 6 to day 10, 6 mg/d from day 11 to day 13, and 4 mg/d from day 14. From day 15, 50 mg/d of P was given, and the dose was increased to 100 mg/d from day 17 (33).…”
Section: Materials and Methods Patientsmentioning
confidence: 99%